HOWL-OWEEN! - Mercer, Sienna (London : Egmont, 2015)
It's Halloween, but twins Daniel and Justin aren't about to be spooked by ghosts and pumpkins - after all, one of them is a werewolf! But there's still plenty to be scared about - like knowing when to hold your new girlfriend's hand, and having to swap identities to keep your biggest family secret safe.
Keywords: Children's stories, English